UNDERSTANDING THE INFLUENCE OF LEARNING STYLE CATEGORIZATION ON SPOKEN ENGLISH PROFICIENCY: A QUALITATIVE EXPLORATION AT SMAN 1 KEBOMAS, GRESIK - Belintang Yugus N.P; Nirwanto Ma’ruf; Paulina (International Journal of Teaching and Learning, 2026)
At SMAN 1 Kebomas, this study examines the connection between spoken English competency and learning approaches, It aims to: explore how individual learning styles relate to spoken English proficiency through qualitative methods like interviews and observations and investigate students'' personal experiences and perceptions of how their learning style impactstheir ability to express themselves in English through interviews and discussions. Embarking on a comprehensive journey, this study aims to elucidate intricate relationship between individual learning style categorizations , spoken English proficiency among students at SMAN 1 Kebomas The researcher . utilize several instruments get the data. The small group interviews and observation and survey are the research instruments will be employed in this study : Small Group Interview & Observation. results conclusion practising speaking abilities through active usage of English is beneficial, particularly for individuals with a kinesthetic style. research findings at SMAN 1 Kebomas confirm Triananda, (2022) by demonstrating kinesthetic students may enhance their speaking skills through active practice techniques. . Observe and mimic language usage in movies and plays. Gain exposure to genuine spoken English through listening exercises This research found that auditory and kinesthetic learning significantly impact students'' spoken English at SMAN 1 Kebomas Gresik. Auditory benefit from listening-based activities like podcasts and discussions, while kinesthetic learners thrive with hands-on activities like role-playing and simulations. Both styles benefit from audio input, but kinesthetic learners require physical engagement to solidify their learning. Teachers are able to create more interesting and successful learning experiences by taking these learning types into consideration.